2013
DOI: 10.6000/1927-5129.2013.09.17
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteinases Secreted by Two Isolates of the Fungus Alternaria solani

Abstract: It is well-known Alternaria solani Sorauer is the causative agent of alternariosis. In this paper, serine proteinases secretion by two genetically related isolates of the fungus, collected from potato and tomato plants grown in central Russia have been studied. The data clarify functions of these enzymes in the process of pathogenesis in which they can play a pivotal role. Also, the data should allow classifying Alternaria’s strains more precisely. It was found that the two isolates produced trypsin-like and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The previous data [11] indicate the absence of the clear correlation of the serine exoproteases composition with the nature of host plants.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The previous data [11] indicate the absence of the clear correlation of the serine exoproteases composition with the nature of host plants.…”
Section: Resultsmentioning
confidence: 94%
“…Simultaneously, such medium would be a model for studying the infection process. It was also demonstrated that during Alternaria growth in this medium, fungi produced extracellular proteinases with the slightly alkaline activity optimum [11]. Figure 1 shows the results of the study of proteinases excretion by the mentioned 13 isolates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations